Linear perspective in the age of Galileo: Lodovico Cigoli's Prospettiva pratica - Camerota, Filippo -1960; Frost, Catherine (Florence Olschki, 2010)
Ludovico Cigoli's 'Prospettiva pratica' (Practical Perspective) is both a work of artistic literature and an extraordinary scientific document on the role attributed to the representation of the visible world in Galileo's research. Composed by one of the painters closest to Galileo in the years of the great astronomical discoveries (1610-1613), the treatise illustrates decisive themes for perspective drawing, from orthogonal projections to shadow projection, from theatrical scenes to the use of mechanical instruments.
Cigoli and the art of "divine" sight / Martin Kemp -- The Prospettiva pratica and Cigoli's reputation / Miles Chappell -- Cigoli's "master in perspective" -- The manuscript -- Cigoli's contribution to the codifying of Renaissance perspective -- Criteria of transcription -- Prospettiva pratica. Manuscript 2660 a in the Gabinetto dei Disegni e delle Stampe degli Uffizi : transcription and notes.
Includes bibliographical references and index.
Includes the original Italian text of Ludovico Cigoli's Prospettiva pratica with introduction and commentary in English and English translations.
Keywords: Cigoli, Ludovico Cardi da -- 1559-1613; Architecture